Implantación de un sistema de seguridad para el acceso inalámbrico a la red de la Universidad Nacional de Loja utilizando software libre. - Flores Gallardo, Fabricio Alejandro (2012)
At the Universidad Nacional de Loja, the implementation of a security system for the wireless access to data network using free software is very important, because there is currently no security system that controls access to the use of the internet service. This final career project (PFC) describes the implementation of a RADIUS server, which with a captive portal will provide the necessary assurances for access to the network of the Universidad Nacional de Loja through wireless access points, allowing only authorized personal (username and password) can access the Internet service. The implementation of the server, in addition to improving network security, helps the wireless proxy server is not overloaded with request, improving the quality of service and improved connection times by users. The operating system on which the solution has been implemented is GNU / Linux, Ubuntu Server 12.04, because it offers stability and support software solutions raised and is required to maintain a standard for the servers used in Unidad de Telecomunicaciones e Información. For the RADIUS server software was used FreeRADIUS version 2.1.10 (see Resultados section 1.1.13. Determinación de las herramientas adecuadas para la solución del problema). For captive portal Coovachilli version 1.2.6 was chosen as it is released under a free license GPL (see Anexo 8). Furthermore, Coovachilli works perfectly with a RADIUS server, and has a community that collaborates in the development of the application (see Resultados section 1.2.12. Selección del portal cautivo adecuado). For the authentication process, we use the Web Services of the Sistema de Gestión Académica of Universidad Nacional de Loja, (see Resultados section 1.2.5 Autenticación de FreeRADIUS con el Web Services del Sistema de Gestión Académico ) and proceeded to respective testing the security system in the Área de la Energía, las Industrias y los Recursos Naturales no Renovables (see Resultados section 1.4.3.2 Results section. Pruebas en el Área de la Energía las Industrias y los Recursos Naturales no Renovables).